Fear of food prospectively predicts drive for thinness in an eating disorder sample recently discharged from intensive treatment. (December 2017) - Levinson, Cheri A.; Brosof, Leigh C.; Ma, Jackie; Fewell, Laura; Lenze, Eric J.
Abstract: Fears of food are common in individuals with eating disorders and contribute to the high relapse rates. However, it is unknown how fears of food contribute to eating disorder symptoms across time, potentially contributing to an increased likelihood of relapse. Participants diagnosed with an eating disorder ( N  = 168) who had recently completed intensive treatment were assessed after discharge and one month later regarding fear of food, eating disorder symptoms, anxiety sensitivity, and negative affect. Cross lagged path analysis was utilized to determine if fear of food predicted subsequent eating disorder symptoms one month later. Fear of food—specifically, anxiety about eating and feared concerns about eating—predicted drive for thinness, a core symptom domain of eating disorders. These relationships held while accounting for anxiety sensitivity and negative affect. There is a specific, direct relationship between anxiety about eating and feared concerns about eating and drive for thinness. Future research should test if interventions designed to target fear of food can decrease drive for thinness and thereby prevent relapse. Highlights: Fear of food predicted drive for thinness across one month. This relationship was not accounted for by anxiety sensitivity or negative affect. There is a specific, direct prospective relationship between fear of food and drive for thinness. Intervening on fear of food may prevent drive for thinness.